PENINGKATAN NILAI PRODUKTIVITAS PAKAN BERNUTRISI TINGGI DENGAN TEKNOLOGI FERMENTASI JERAMI PADI MENGGUNAKAN RUMEN TERNAK TERMODIFIKASI UNTUK PENINGKATAN BERAT BADAN KAMBING - Susanti, Rina; Shamad, Zulfaini; Sathalica, Cepryana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Ruminant livestock productivity in Indonesia still faces major challenges, particularly due to limited feed quality during the dry season and insufficient utilisation of agricultural waste. This community service programme aims to improve goat productivity through rice straw fermentation technology using modified goat rumen. The activities were carried out in the